Isotopic evidence for dietary variability among eastern Africa’s first pastoralists - Kendra L. Chritz; Elizabeth A. Sawchuk; Mary E. Prendergast; Scott A. Blumenthal; Thure E. Cerling; Julie Dunne; Steven T. Goldstein; Katherine M. Grillo; Anneke Janzen; Purity Kiura; Julia Lee-Thorp; Marta Mirazón Lahr; et al. (Proceedings of the National Academy of Sciences, 2026)
During the terminal Pleistocene through Holocene, changes in dietary diversity signaled fundamental shifts in the way humans related to food resources in many parts of the globe. To understand local and regional dietary variation across the transition to food production in Kenya and Tanzania, we compare isotopic values of biological tissues (tooth enamel and bone collagen) from 111 ancient foragers and herders dated ~9,500–230 B.P., alongside isotopic data from contemporary eastern Africans, and contextualize these findings with ancient leaf wax and ceramic lipid residues. Fisher-foragers had remarkably diverse approaches to subsistence, and the earliest pastoralists in Kenya’s Turkana Basin ~5,000 years ago retained dietary diversity amid major environmental and cultural changes. The shift to more specialized pastoralist diets did not occur until a millennium after the initial introduction of livestock.